Effects of an Injury Prevention Program in CrossFit Athletes: A Pilot Randomized Controlled Trial - Martínez-Gómez, Rafael; Valenzuela, Pedro L.; Moral-González, Susana; Lucia, Alejandro; Barranco-Gil, David (International Journal of Sports Medicine, 2021)
The present study aimed to assess the effects of an injury prevention program in CrossFit athletes. Thirty-two CrossFit athletes were randomized to either an intervention group (n=16), that performed mobility and stability exercises during the warm-up of all CrossFit sessions for a 10-week period or to a control group (n=16) that kept performing their usual warm-up. Incidence of injuries (primary outcome) as well as average training loads, fatigue and pain perception were registered during the study. The overall injury incidence rate was 0.04 per 1000 training hours, with no differences between groups (p>0.05). Similarly, no between-group differences were found for injury severity, nor for average training volume, intensity, training load, pain, or fatigue perception during the study (all p>0.05 with trivial-to-small effect sizes). In summary, a 10-week injury prevention program consisting of stability and mobility exercises provided no benefits on injury rates, fatigue and pain perception in recreational CrossFit athletes. Further research might corroborate the preliminary evidence reported here.
Keywords: injuries; power; strength; physical performance